The relationship between Intima-Media Thickness and Carotid Plaque Characteristics with Incidence and Severity of Premature Coronary Artery Disease: Intima-Media Thickness and PCAD - Haji Aghajani , Mohammad; Raoufi , Masoomeh; Sadeghi, Roxana; Arefinia , Faezeh; Parsa Mahjoob, Mohammad (Novelty in Biomedicine, 2023)
Background: Carotid intima media thickness (CIMT) and carotid plaque can predict premature coronary heart disease (PCAD) in patients hospitalized due to coronary artery disease or undergoing therapeutic interventions. This study aimed to determine the relationship between intima media thickness and carotid plaque characteristics with the incidence and severity of premature coronary artery disease. Materials and Methods: The current study was an analytical cross-sectional study conducted on patients referred to Imam Hossein Hospital in 2021-2022 who underwent coronary angiography. Patients were classified into two groups with coronary artery involvement and the group without evidence of significant coronary involvement. Then the data of patients, such as sex, age, risk factors of cardiovascular diseases, and clinical history of individuals, were collected through interviews and aspects related to carotid intima media thickness and plaque formation through a specialized review of reports. Results: A total of 59 women (%59) and 41 men (%41) participated in this study. The mean age was 51.50±9.54. The results of this study showed that there was a direct (positive) and significant correlation between carotid intima media thickness factors, including right and left carotid intima-media thickness, right and left carotid intima media thickness scores, and the number of carotid plaques with increasing severity of coronary artery involvement (P-values<0.05). There was a statistically significant correlation between carotid plaque number and severity of coronary artery disease (P-value<0.05). Conclusion: CIMT has a significant correlation with PCAD, and in patients at risk of PCAD, measurement of CIMT was a suitable method.